2021
DOI: 10.1038/s41598-021-83578-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between fluoroquinolone resistance and MRSA genotype in Alexandria, Egypt

Abstract: Antimicrobial stewardship isn’t strictly observed in most Egyptian hospitals, raising antibiotic resistance. Epidemiology of Egyptian MRSA isolates, or associations with resistance to other antibiotics remain largely unknown. We identified MRSA genotypes in Alexandria Main University Hospital (AMUH) and investigated rates of moxifloxacin resistance, an alternative MRSA treatment, among different genotypes. Antibiotic susceptibility of 72 MRSA clinical isolates collected in 2015 from AMUH was determined by disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
(45 reference statements)
5
20
1
Order By: Relevance
“…In addition, published studies show that MRSA strains similar to W333 are common in Egypt. For example, fexA-positive ST5-VI-t688 MRSA isolates constituted 6% of MRSA isolates obtained from human patients in a hospital in Alexandria, Egypt [37], and fexA-positive CC5-MRSA-V/VT were recovered from milk of cattle and buffaloes with mastitis also in Egypt [38,39] indicating the widespread distribution of fexA in MRSA in diverse hosts in the country. The presence of the fexA-positive clone in cattle and buffaloes with subclinical mastitis poses potential risk to humans since the consumption of milk obtained from cattle or buffaloes with subclinical mastitis can be a potential source of transmission of resistant S. aureus to humans [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, published studies show that MRSA strains similar to W333 are common in Egypt. For example, fexA-positive ST5-VI-t688 MRSA isolates constituted 6% of MRSA isolates obtained from human patients in a hospital in Alexandria, Egypt [37], and fexA-positive CC5-MRSA-V/VT were recovered from milk of cattle and buffaloes with mastitis also in Egypt [38,39] indicating the widespread distribution of fexA in MRSA in diverse hosts in the country. The presence of the fexA-positive clone in cattle and buffaloes with subclinical mastitis poses potential risk to humans since the consumption of milk obtained from cattle or buffaloes with subclinical mastitis can be a potential source of transmission of resistant S. aureus to humans [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…We found that MRSE isolates recovered from goat nasal swabs possessing ST35 genotype have previously also been recovered from a patient in Iraq, shared bicycle in China, birds of prey in Portugal, associated with farmers and hospital-associated isolates in Belgium, clinical isolates in Portugal, environmental sources from Germany as well as isolates recorded on pubMLST (accessed 18 November 2021) from a human source in Germany, South Korea, and Russia ( 41 47 ). Another genotype identified in our study, ST153 has been previously reported in isolates recovered from samples of catheter-related bloodstream infections in Belgium, nasal swabs, subgingival sites and oral rinse in Ireland and an isolate recovered from human samples in Ireland, the USA, and Latvia ( 44 , 48 , 49 ).…”
Section: Discussionmentioning
confidence: 82%
“…All isolates were identified using conventional methods, such as Gram staining, growth on and fermentation of mannitol salt agar (MSA; Oxoid Ltd., England), growth on DNase agar, and slide coagulase testing using Dryspot Staphytect Plus (Oxoid Ltd., England), and confirmed using matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) with the MALDI Biotyper 3.0 software (Bruker Daltonik, USA). The isolates were further classified as either hospital-acquired or community-acquired infections based on a 48-h window between the dates of patient admission and isolate collection ( 57 ).…”
Section: Methodsmentioning
confidence: 99%